Color stability of pigmented maxillofacial prosthetic silicone elastomer with and without filler incorporation subjected to outdoor weathering - a digital evaluation - Rashid, Qazi Farah (2021)
Clinical success of elastomeric prostheses is constantly challenged by local environmental weathering and lighting variations, which eventually leads to color degradation. Various methods, such as filler infusion have been implemented to slow down physical color degradation process. However, with the recent shift to complete digitization, virtual perception and acceptability have become just as important for clinical success as functional rehabilitation owing to a boom in digital communications via photographs and video recordings. Therefore, digital photography now plays a key role in treatment planning, patient motivation and diagnostic outcomes in everyday dental practice. The current study aims to digitally evaluate the influence of outdoor weathering and filler inclusion on the color stability of pigmented silicone elastomers. Two maxillofacial prosthetic silicone elastomers (A-103 and A-2006) were colored with two oil-based pigments [blush (FI-SK13) and honey (FI-SK09)] to simulate skin tone according to the ‘Fitzpatrick scale’. 216 pigmented silicone samples [A-103(blush), A-103(honey), A-2006(blush), A-2006(honey)] were derived from custom 3D-printed templates. The influence of Malaysian weather on color degradation of the aforementioned pigmented silicone elastomers was evaluated by weathering 72 samples. Nano-filler particle silicon dioxide (SiO2) was infused within an additional 72 pigmented samples that were also weathered. Weathering of the samples was done on a custom-made outdoor exposure rack for 4 months in Malaysian weather. 72 samples were not weathered and were subjected to a humidifier at a temperature of 20⁰C ±5⁰C with relative humidity of 70 ±5%. The samples were photographed 2 times; once before weathering (baseline) and once after weathering by a professional digital camera in a custom-made standardized studio setup. The photographs were electronically color calibrated by using a computerized ‘Macbeth color chart’ and CIELAB values were digitally derived by using Adobe-Photoshop Lightroom Classic CC. Color change (ΔE) after weathering was then evaluated for all samples. Independent Sample t-test and Analyses of Variance (2-way and 3-way) were performed to make statistical comparisons. A-103 (honey) and A-2006 (blush) exhibited no significant (P>.05) color differences after weathering with significant interaction (P<.001) effects observed between all silicone groups and pigments. Incorporation of nano-filler showed no significant (P>.05) difference after weathering but had significant interactions (P<.001) with pigment and silicone groups. The findings suggest that, in tropical weathering conditions, prosthesis made with A-103 honey pigments or A-2006 with blush pigments can produce more color resilience and SiO2 only protect the silicone if A-103 and blush pigment combination was used.